2020
DOI: 10.32890/mmj.22.2018.9677
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Service Quality on Customer Loyalty of Generation Y – An Empirical Investigation on Superstores in Bangladesh

Abstract: Today, retailers have been struggling to retain their existing customers in the face of severe competition in their business operations. By expanding the service quality, retailers will be able to stand out among the other businesses and create the opportunity to strengthen customer loyalty, particularly within the younger generation. The aim of this study is to propose and empirically investigate the mechanism of increasing customer loyalty of Generation Y (Gen Y) toward superstores by means of enhancing serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…The path coefficient value indicates the direction of positive influence, which means that the better the perception of reliability, the more online seller loyalty increases. The results of this study are in line with previous researchs [11,16,30]. Reliability is perceived as the provision of services that are provided reliably, precisely, and guaranteed to achieve customer satisfaction which then encourages the expansion of trust and loyalty to services [31].…”
Section: Discussionsupporting
confidence: 88%
“…The path coefficient value indicates the direction of positive influence, which means that the better the perception of reliability, the more online seller loyalty increases. The results of this study are in line with previous researchs [11,16,30]. Reliability is perceived as the provision of services that are provided reliably, precisely, and guaranteed to achieve customer satisfaction which then encourages the expansion of trust and loyalty to services [31].…”
Section: Discussionsupporting
confidence: 88%
“…Through the existence of the high word of mouth from consumers on the quality of service at the Pantai Cermin tourism location, it implies that the quality of the services they have is good, this causes the good word of mouth for good service to be able to influence potential consumers who then succeed in making consumers interested and decide to make a purchase decision on the service they want to buy. The results of the study are in line with the research results of which concluded that word of mouth can significantly become an intervening variable on the influence of service quality on consumer purchasing decisions [44][45] [46].…”
Section: Effect Of Service Quality On Purchase Decisions Through Elec...supporting
confidence: 81%
“…Furthermore, five dimensions of service quality namely Problem solving, reliability, policy, Personal and physical aspect were taken into consideration to determine their overall impact as service quality on customer loyalty. The findings revealed that all the dimensions possess a significant impact on customer loyalty therefore retailers utilizing appropriate service quality could result customer loyalty in their favor (Didarul Alam, 2020). In light of the above discussion, we can propose the following hypothesis:…”
Section: Service Quality and Customer Loyaltymentioning
confidence: 87%